Electrochemical grooving of tube inner walls with emphasis on feed strategy and multi-pass effects on material removal and groove geometry - Semih Ekrem Anil; Hasan Demirtas (PLoS ONE, 2025)
Electrochemical (EC) grooving minimises tool wear and residual stress when machining hard-to-cut tube materials. This study examines how the number of passes and tool feed direction affect material removal rate (MRR) and removed area (RA) in Stellite 21 tubes. Two feed strategies were tested: Unidirectional Electrolyte Flow (UEF), where the tool moves entirely opposite to the electrolyte flow; and Hybrid Electrolyte Flow (HEF), where the tool first moves against and then with the flow direction. Results showed that the highest MRR values (26.67 mg/s for HEF, 24.8 mg/s for UEF) were observed with two passes, but dropped significantly at four and six passes due to extended machining time. RA increased along the tool path under UEF, reaching up to 327% at the tool exit. Flow simulations revealed that low velocity and conductivity at the tool entry caused under-machining, whereas turbulence at the exit enhanced material removal. These findings offer valuable guidance for optimising EC grooving processes in aerospace and biomedical applications.